2016
DOI: 10.4012/dmj.2015-363
|View full text |Cite
|
Sign up to set email alerts
|

Dentin bonding performance and interface observation of an MMA-based restorative material

Abstract: The purpose of this study was to evaluate bonding performance and dentin interface acid resistance using a 4-META/MMA-TBB based restorative material (BF) compared to a conventional 4-META/MMA-TBB resin cement (SB), and the effect of sodium fluoride (NaF) addition to the materials. Dentin surfaces were treated with 10% citric acid-3% ferric chloride (10-3) or 4-META containing self-etching primer (TP), followed by application of BF or SB polymer powders with or without NaF, to evaluate microtensile bond strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The bond strength of RMGIC can be enhanced by improving the resin bonding mechanism because of its resin component, as well as the quality of the hybrid layer. Self Conditioner was reported to increase the bond strength of RMGIC 21,22) , it contains both 4-META, a functional monomer that chemically interacts with the HAp in dentin 31,32) , and HEMA, which improves the dentin wettability and RMGIC spread and penetration into the dentin 26) . When combined, these factors can improve the quality of the hybrid layer 33) which may be the major source of the enhanced bond strength 22) .…”
Section: Discussionmentioning
confidence: 99%
“…The bond strength of RMGIC can be enhanced by improving the resin bonding mechanism because of its resin component, as well as the quality of the hybrid layer. Self Conditioner was reported to increase the bond strength of RMGIC 21,22) , it contains both 4-META, a functional monomer that chemically interacts with the HAp in dentin 31,32) , and HEMA, which improves the dentin wettability and RMGIC spread and penetration into the dentin 26) . When combined, these factors can improve the quality of the hybrid layer 33) which may be the major source of the enhanced bond strength 22) .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported no difference in bond strength between Teeth Primer and Green Activator treatments. 25 In the pilot study, no obvious change in fracture surface properties was observed with the Teeth Primer treatment alone after smear layer removal. Therefore, in this study, only the group immersed in Super-Bond-activated liquid after the Teeth Primer treatment was considered the experimental group.…”
Section: Discussionmentioning
confidence: 82%
“…After the teeth were stored in deionized water at 37 °C for 24 h 32 , the bonded teeth were longitudinally sectioned under a water-cooled diamond saw (Isomet 4000 Linear Precision Saw, Buehler, USA) to produce slabs with a thickness of 1.0 mm. Three slabs from each tooth were sectioned again to prepare beams with a dimension of 1.0 mm × 1.0 mm.…”
Section: Methodsmentioning
confidence: 99%